Imidazolidin-4-one derivatives of primaquine as novel transmission-blocking antimalarials - Araujo, MJ (2015)
Imidazolidin-4-one derivatives of primaquine were synthesized as potential double prodrugs of the parent drug. The title compounds inhibit the development of the sporogonic cycle of Plasmodium berghei, affecting the appearance of oocysts in the midguts of the mosquitoes. The imidazolidin-4-ones are very stable, both in human plasma and in pH 7.4 buffer, indicating that they are active per se. Thus, imidazolidin-4-ones derived from 8-aminoquinolines represent a new entry in antimalarial structure-activity relationships.